Prevalence of Chlamydia Trachomatis among pregnant women - شاهين, عبير; يازجي, هيثم (Latakia University Journal -Medical Sciences Series, 2022)
Chlamydia trachomatis is one of the most common sexually transmitted infections. And due to the lack of previous studies on its prevalence among pregnant women in our country, we conducted this study to determine it.The study included 200 pregnant women attending the Department of Obstetrics and Gynecology at Al-Assad University Hospital in Lattakia, IgG- antibodies specific to Chlamydia trachomatis was detected by enzyme-linked immunoassay ELISA. The results showed that the prevalence of Chlamydia trachomatis in pregnant women was 4.5%, and the prevalence was higher in young pregnant women at the age of less than 25 years, A relationship was found between Chlamydia trachomatis infection and a history of miscarriage, premature birth. We did not find an association with the income level or educational level of pregnant women as well as with clinical symptoms. The study showed that a significant number of pregnant women were exposed to Chlamydia trachomatis, and it is important to conduct a routine survey for pregnant women under the age of 25 to detect infection and early treatment, especially in the presence of other risk factors.